Diretrizes para implantação de sistemas de infraestrutura verde em meio urbano: estudo de caso da cidade de Ribeirão Preto SP - Santos, Anelise Sempionato Souza (2014)
It deduces, nowadays, that one of the biggest challenges to be overcome by planning and urban management is the condition between the conservation of natural resources committed by the process of urbanization and the urban development. This lead to be necessity of developing strategies that provides control conditions and reverse the effects of the socio environmental degradation, as in the case of urban flooding and irregular settlements in conservation areas. From this context stands out the green infrastructure, a system based in environmental urban planning, which offers the perspective of upgrading the urban environment through the development of hybrid networks, that links green spaces and surface water areas. Through analyses of urban landscapes they are identified the socio environmental conditions and they establish strategies using specific planning to guarantee the existence, the recovering and expansion of natural resources in urban spaces. Thus the concept of green infrastructure comes from the idea that natural spaces fulfill infrastructure function, consolidating a landscape of high performance while offering environment benefits. To that situation, it uses several types that enable the conservation of natural ecosystem and their functions: climate regulations, soil permeability, aquifer supply, filtering the storm water, controlling the air and noisy pollution, increased by biodiversity and recreational areas, promotion of nom motorizing mobility, among others. Therefore, this study aims to define the real methods to introduce the system of green infrastructure in a geographic division in urban area of Ribeirão Preto SP, so that it is possible to establish to this area a model of occupation to mitigate negative environmental impacts caused by urban expansion. It will be useful as an example for other cities to get success when they consider this important aspect in their planning to urban space.